HOW SERBIAN LOCAL TOURIST ORGANIZATIONS USE FACEBOOK - Ćamilović, Dragana (The Business of Tourism, 2020)
The use of the Internet, and particularly social networks, has changed the way people inform themselves about potential tourist destinations today. People are often browsing the Internet to find inspiration for their next trip. A nice photograph or a video posted on a Facebook page, for example, can motivate them to further explore the destination and become interested in visiting it. Since local tourist organizations in Serbia play an important role in promoting and supporting tourism on a local level, they need to use the marketing potential of social networks to its fullest. This paper provides an overview of the most commonly used social networking services and the benefits of their use. It also sheds light on the use of Facebook by the local tourist organizations of popular Serbian destinations. The author has investigated Facebook pages of five Serbian local tourist organizations and conducted a comparative analysis according to the number of their fans (i.e., total page likes), total page likes growth comparing to the previous week, the number of their posts in the observed week, and the engagement rates of their fans (in the observed week).